The Effect of Mirror Exercise and Massage on the Facial Functional Ability of Bell's Palsy Patients in the Anugerah Sehat Physiotherapy Practice - Silitonga, Santo Damerius; Naibaho, Eka Nugraha V. (CV. Devitara, 2023)
Disorders that occur in nerves and muscles are a problem that is often encountered in society and one of them is facial nerve dysfunction that can affect a person's quality of life called Bell's Palsy. Improving the functional ability of Bell's Palsy patients is managed physiologically, namely patients are given massage and education such as mirror exercises. The purpose of the study was to determine the effect of mirror exercise and massage on the facial functional ability of Bell's Palsy patients in the practice of Physiotherapy Anugerah Sehat. The type of research used is a quantitative type of research, with the research design used is Quasi Experimental with a pre-test and post test one group approach. This research was carried out at the Anugerah Sehat Physiotherapy Practice in April 2023. The population in this study is 30 Bell's Palsy patients.The sampling technique in this research is Total Sampling. Scale used in the assessment of facial functional ability with Ugo Fisch. Bivariate analysis uses the Paired Sample T Test. The results of the research on the frequency distribution of facial functional abilities of Bell's Palsy patients before being given the Mirror Exercise and Massage modalities, the majority had moderate category facial functional abilities at a value of 30-70 as many as 27 people (90%), the frequency distribution of facial functional abilities of Bell's Palsy patients after being given the Mirror Exercise modality and Massage, the majority of whom had normal facial functional abilities at a value of 70-100 as many as 25 people (83.3%), there was an effect of mirror exercise and massage on the facial functional ability of Bell's Palsy patients in the Anugerah Sehat Physiotherapy Practice with a significant value (2-tailed) 0.000<0.05.